Camille Lemonnier poète en prose ou le portrait de l’artiste en faussaire - Alessio Baldini (Revue Italienne d'Etudes Françaises)
Based on a study of a group of prose poems found in Musée des deux mondes that have not been published in volume, the aim of this article is to situate Camille Lemonnier in the landscape outlined by the French prose poem in the second half of the nineteenth century. The scientific approach of this essay is therefore twofold: on the one hand, documentary, as it aims to give an account of a little-known, even rare, literary production; on the other hand, critical, as it aims to study the stylistic and rhetorical tendencies of this production in the light of the artistic motif that is grafted onto it.